Pemanfaatan Limbah Cangkang Rajungan (Portunus pelagicus) sebagai Produk Pangan di Kabupaten Cirebon - Muhammad Umar Al Faruqi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Small crab is one of the mainstay export commodities of Indonesian fisheries. Large crab production is followed by a large amount of crab waste. Small crab shell waste can have an impact on environmental pollution if not properly managed. Processing crab shell waste into a food product that has a sale value can be a solution for crab shell waste management. Shell processed products also have nutritional value. Small crab shell waste can be processed into various products such as paste, broth and crackers. Small crab paste with 25% palm sugar concentration is the best treatment because it produces a sweet taste that matches the thick texture and strong aroma of small crab. The use of filtrate as broth produces broth that is smooth and soluble in water. The appearance of the broth produced is white and clean. Small crab crackers with 15% broth powder concentration produce crackers with a small crab flavor. The texture and appearance produced are also no different from other commercial crackers. The simple manufacturing process is expected to increase the interest of the community in producing processed crab shell products.